Pengaruh Nitrogen dan Silika terhadap Pertumbuhan dan Perkembangan Spodoptera litura (Lepidoptera: Noctuidae) pada Kedelai - Dina Wahyu Trisnawati; Nugroho Susetya Putra; Benito Heru Purwanto (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2017)
A study was conducted to establish the indirect effects of nitrogen (N) and silicon (Si) on the growth and development of Spodoptera litura on soybean. A full-factorial experiment was arranged in 4x2 factors: first factor was nitrogen with varied doses of 0, 25, 50, and 100 kg/ha; second factor was silicon at 0 and 200 g/m2. The results demonstrated that the application of N and Si indirectly affected the growth and development of S. litura including leaves consumed, weight of larvae, weight of pupal, fecundity and survivorship. In addition, combination of nitrogen and silicon also affected the growth and development of soybean as evidenced by the decreased absorption of Si by soybean following the application of N, while the application of Si combined with high nitrogen doses decreased the absorption of Si. It was also observed that the effect of N was not significant on the growth and development of S. litura.  The application of Si with the high N doses, however, decreased the growth and development of S. litura. It is, therefore, concluded that the mechanism of relationship between N and Si on S. litura could not be explained only by quantifying the absorption value of N and Si.